2022
DOI: 10.3389/fpsyg.2022.859210
|View full text |Cite
|
Sign up to set email alerts
|

University Students’ Successive Development From Entrepreneurial Intention to Behavior: The Mediating Role of Commitment and Moderating Role of Family Support

Abstract: University students having high entrepreneurial intention while not transferring into actual entrepreneurial behavior is a contradictory issue in need of in-depth research. To explore the successive development mechanism of the entrepreneurial process, this study constructed a moderated mediation model to examine whether entrepreneurial commitment from three dimensions (affective, behavioral, and continuance) mediated the relationship between entrepreneurial intention and behavior, and whether this mediating p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 78 publications
0
1
0
Order By: Relevance
“…This relationship is new in knowledge but has support from existing studies. According to the study by Mei et al (2022), the student's entrepreneurial intention directly influences their entrepreneurial behavior. Majeed et al (2021) confirmed SEI strongly influences the entrepreneurial behavior of the student to work in the future.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This relationship is new in knowledge but has support from existing studies. According to the study by Mei et al (2022), the student's entrepreneurial intention directly influences their entrepreneurial behavior. Majeed et al (2021) confirmed SEI strongly influences the entrepreneurial behavior of the student to work in the future.…”
Section: Discussionmentioning
confidence: 99%
“…This relationship is new in knowledge but has support from existing studies. According to the study by Mei et al . (2022), the student’s entrepreneurial intention directly influences their entrepreneurial behavior.…”
Section: Discussionmentioning
confidence: 99%
“…According to the theory of innovation ecology, the link between the subjects and their environment is vital. By integrating the creative atmosphere in schools and the innovative environment of the enterprises and society, an effective mechanism of industryuniversity alliances can be developed, which is crucial to cultivating innovative talents (Lin, 2018;Mei et al, 2022).…”
Section: Literature Review Creativity and Innovative Thinkingmentioning
confidence: 99%